1976
DOI: 10.1161/01.str.7.6.569
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical dilation of the large cerebral arteries in hypocapnia in man.

Abstract: SUMMARY By grouping patients who had carotid angiograms under unusually carefully monitored conditions it has been shown that hypocapnia is associated with vasodilatation at low blood pressure but not at high blood pressure. The mechanism is discussed in general terms and it is suggested that the hypocapnic vasodilatation may be a response to cerebral hypoxia and may be transmitted via an intracerebral autonomic pathway. Clinical and angiographical diagnoses are given for SO patients.IN THE BABOON there is ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 7 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…Changes of this magnitude have been observed angiographically when arterial blood pressure increased from < 7 6 to > 100 mm Hg in patients under general anesthesia and moderate hypocapnia. 19 The differences found in the present series might, therefore, reflect predictable individual variation. Although difficult to evaluate statistically, the linear relation between flow and blood velocity did not seem to be seriously offset by moderate therapeutic doses of metaraminol or thiopentone.…”
Section: Blood Velocity Vs Flow Volumementioning
confidence: 57%
“…Changes of this magnitude have been observed angiographically when arterial blood pressure increased from < 7 6 to > 100 mm Hg in patients under general anesthesia and moderate hypocapnia. 19 The differences found in the present series might, therefore, reflect predictable individual variation. Although difficult to evaluate statistically, the linear relation between flow and blood velocity did not seem to be seriously offset by moderate therapeutic doses of metaraminol or thiopentone.…”
Section: Blood Velocity Vs Flow Volumementioning
confidence: 57%
“…The underlying regulatory mechanism is rather complex and involves different biochemical mediators like K + , H + , and adenosine (see Hamann & del Zoppo, 1994; Kuschinsky, 1991; Villringer & Dirnagl, 1995). In contrast to the small vessels, the diameter of the larger cerebral arteries primarily remains unchanged under varying stimulation conditions (Giller, Bowman, Dyer, Mootz, & Krippner, 1993; Huber & Handa, 1967; Kontos, 1989; Radu & du Boulay, 1976). From these results, it can be concluded that changes in flow velocities in the large basal arteries are not a result of their own vasomotor activity, but reflect changes in the blood demand in their perfusion territories, and thus changes in local neuronal activity patterns.…”
Section: Functional Transcranial Doppler Sonography (Ftcd)mentioning
confidence: 99%
“…24 The diameter of large cerebral arteries such as the MCA, however, remains relatively constant during a reduction of blood pressure. 25,26 Therefore, the changes of flow velocity in the MCA might correlate with the changes of cerebral blood flow. 27 This noninvasive transient hyperemic response test is simple, safe, and reproducible at the bedside and could serve as a marker of CVR.…”
Section: Chao and Leementioning
confidence: 99%